Sustainable Compliant Physical Interaction in a Biped-Wheeled Wearable Machine - Trono, Gaspare; Nicolì, Angelo; Muscolo, Giovanni Gerardo (Frontiers in Mechanical Engineering, 2020)
This paper deals with the problem of the human-machine physical interaction in biped-wheeled exoskeletons and underlines how the symbiosis among humans and machines may increase the sustainability. Only few exoskeletons in the world are designed with wheels, but the evolution of wearable machines in industries and the convenience to use the wheels, underline to give more importance to the novel research sector of biped-wheeled exoskeletons. This paper shows the functional design and simulation of a novel biped-wheeled-wearable machine, including the sustainable compliant physical interaction with the subject on board. In particular, the multibody model of the proposed machine is studied and simulated with the subject model on board, including human-machine compliant interactions. The classical human walking cycle is implemented in the machine varying the speed and the joint compliance of the subject on board, and comparing the torque and power output of the motors of the biped-wheeled exoskeleton. The results of this study underline how the joint compliance of the subject on board of the biped-wheeled exoskeleton may influence the efficiency and the sustainability of the biped-wheeled-wearable machine.